Sound absorption characteristics of Durian husk fibers reinforced polyurethane composite - Masrol, Shaiful Rizal; Ahmad Fauzi, Syahmil Azim; Marsi, Noraini; Kamaruddin, Khairu; Mustaffa, Norrizal (Penerbit UTHM, 2020)
Nowadays sound adsorption is required in most industrial applications. Sound adsorption materials are needed mainly in automotive, production environments and equipment, generating a higher sound pressure leading to a more efficient and economical development. Noise is an important environmental issue in modern society and is increasingly recognized as a pollutant that affects human health and well-being...